INSTITUTIONS OF HIGHER EDUCATION AND THE NEIGHBORHOOD INSTITUTE OF COOPERATION SOCIAL-PSYCHOLOGICAL CHARACTERISTICS - Rakhmatova Xayrikhon Ashiraliyevna (Web of Journals Publishing, 2024)
At its core, any form of theoretical cooperation, regardless of type, inherently possesses socio-psychological characteristics. By considering these socio-psychological traits during the organization and execution of cooperative efforts, desired outcomes can be achieved. Therefore, when planning collaborative activities, it is crucial to shape their content while taking into account these socio-psychological factors to ensure the expected results are met. The cooperation between higher education institutions (HEIs) and the Mahalla Institute exemplifies these socio-psychological characteristics, common to all joint activities. The article explores these features and how they are reflected in the cooperation between the Mahalla Institute and universities.
Keywords: higher education institutions, Mahalla Institute, cooperation, social cooperation, partner entities, social agreement, mutual trust, proactive activity, positive nature of cooperation, mutual assistance, mutual support, purpose, motives, resources, requirements of cooperation, emotional benefits of cooperation, social roles.